Isotopic analysis of sub‐nanogram neodymium loads using new ATONA™ amplifiers. (2nd February 2021) - Reinhard, Andrew; Inglis, Jeremy; Steiner, Robert; LaMont, Stephen; Palacz, Zenon
Abstract : Rationale: Emerging research in the geological and nuclear forensics fields demands increasing analytical precision of isotope ratio measurements with decreasing sample sizes. Here we demonstrate the capability of a newly developed amplification technology to make precise neodymium (Nd) isotopic measurements on 100‐pg standard loads. Methods: The reference materials were analyzed as NdO + to increase the ionization efficiency of the small analyte loads. The Nd isotopic measurements were made using an IsotopX Isoprobe‐T thermal ionization mass spectrometer upgraded with the ATONA™ amplifier system. The ATONA™ amplifier system uses capacitance‐based amplification as opposed to traditional impedance‐based amplification. Results: The long‐term gains of the ATONA™ amplifiers are shown to have less than 1 ppm variability. Repeat measurements of the JNdi‐1 reference material demonstrate the ability of the ATONA™ amplification technology to make measurements of 143 Nd/ 144 Nd ratios with 23 ppm external reproducibility on 100‐pg loads. The effect of increasing integration time on analytical reproducibility is also displayed as increasing integration time from 10 to 30 s reduced the external measurement uncertainty from 37 to 23 ppm. Conclusions: These measurements represent an improvement of more than a factor of 3 in external measurement reproducibility relative to previously published 143 Nd/ 144 Nd measurements of 100‐pg loads. This new technology will allow for the measurement of smaller samples for precise isotope ratios and open new avenues of research in the geological and nuclear forensic communities.